Consumer leather exposure: an unrecognized cause of cobalt sensitization. (12th October 2013) - Thyssen, Jacob P.; Johansen, Jeanne D.; Jellesen, Morten S.; Møller, Per; Sloth, Jens J.; Zachariae, Claus; Menné, Torkil
Summary Background A patient who had suffered from persistent generalized dermatitis for 7 years was diagnosed with cobalt sensitization, and his leather couch was suspected as the culprit, owing to the clinical presentation mimicking allergic chromium dermatitis resulting from leather furniture exposure. Materials and methods The cobalt spot test, X‐ray fluorescence, inductively coupled plasma mass spectrometry and scanning electron microscopy were used to determine cobalt content and release from the leather couch that caused the dermatitis and from 14 randomly collected samples of furniture leather. Results The sample from the patient's leather couch, but none of the 14 random leather samples, released cobalt in high concentrations. Dermatitis cleared when the patient stopped using his couch. Conclusions Cobalt is used in the so‐called pre‐metallized dyeing of leather products. Repeated studies have found high levels of cobalt sensitization, but not nickel sensitization, in patients with foot dermatitis. We raise the possibility that cobalt may be widely released from leather items, and advise dermatologists to consider this in patients with positive cobalt patch test reactions.